Harmonic separator mirror suitable for high power lasers

CN122710437BActive Publication Date: 2026-10-16SHANGHAI GAONENG YU PLATING TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611188146.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-16
Estimated Expiration
2046-08-06

AI Technical Summary

Technical Problem

然而,现有技术在实现上述双波段极端光谱分离时面临多方面的核心矛盾

Benefits of technology

1.本发明通过优化膜系结构,突破传统周期性膜堆的局限,消除了界面相位失配引发的强烈通带干涉波纹,该结构在确保532nm倍频光反射率大于99.9%的同时,将1064nm基频光的表面剩余反射率稳定压制在0.1%以下,大幅提升了激光系统倍频链路的分离效率;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122710437B_ABST
    Figure CN122710437B_ABST
Patent Text Reader

Abstract

This invention discloses a harmonic separation mirror suitable for high-power lasers. The harmonic separation mirror includes a substrate and a film system disposed on one side of the substrate, the film system having an Air|(LH) structure. 15 |Sub. Wherein, H is an HfO2 film layer, and L is a SiO2 film layer; the film system consists of 30 alternating layers stacked from the substrate outwards, with geometric thicknesses of 49.68nm, 92.66nm, 76.73nm, 95.33nm, 55.14nm, 91.02nm, 73.59nm, 93.63nm, 59.84nm, 91.14nm, 70.41nm, 91.37nm, 63.58nm, 93.21nm, 67.21nm, 88.33nm, 66.97nm, 96.42nm, 64.19nm, and 84.2nm respectively. 2nm, 70nm, 100.57nm, 62nm, 78.77nm, 72.54nm, 105.11nm, 61.14nm, 71.99nm, 74.63nm, 192.81nm; This invention, by optimizing the film structure and coordinating specific ion beam-assisted and magnetron sputtering deposition processes, eliminates interface passband interference ripples and metastable absorption defects in the film layer. It not only achieves spectral control with a transmittance of <0.1% at 532nm and >99.9% at 1064nm, but also has an absorption loss of <10ppm, significantly improving the laser damage resistance threshold and high-energy thermal stability of the device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of optical element technology, and more specifically to a harmonic separation mirror suitable for high-power lasers. Background Technology

[0002] High-power solid-state lasers are widely used in precision machining, optoelectronic countermeasures, and scientific research facilities. Their frequency doubling links require harmonic separators to efficiently separate the fundamental and frequency-doubled light. Taking an Nd:YAG laser system as an example, the fundamental 1064nm infrared light is frequency-doubled by a nonlinear crystal to produce 532nm green light. The harmonic separator needs to achieve a reflectivity greater than 99.9% for the 532nm frequency-doubled light for refracting and output, while simultaneously achieving a residual reflectivity of less than 0.1% for the 1064nm fundamental light to ensure efficient transmission. However, existing technologies face several core challenges in achieving this dual-band extreme spectral separation.

[0003] Regarding the damage threshold of 532nm high-reflectivity film stacks, existing antireflective mirrors have a low laser damage threshold when subjected to direct irradiation with high-energy green light, making it difficult to maintain stable operation for extended periods at high energy flux densities approaching the crystal damage limit. Regarding thermal failure caused by residual absorption, even if the film layer is in a high-reflectivity state at 532nm, the local enhancement effect of the standing wave field within the film stack can still excite intrinsic absorption in the material. Existing high-reflectivity films often exhibit residual absorption of tens to hundreds of ppm in this band, leading to significant thermal deposition under green light cycling power of around 5 kW, causing thermal lensing, wavefront distortion, and even film cracking. The surface temperature rise of the substrate is difficult to control below 35°C. Regarding antireflection compatibility at 1064nm, the system requires the same element to have extremely low residual reflectivity in the fundamental frequency band. Traditional single-sided antireflection films cannot simultaneously achieve high reflectivity at 532nm, while conventional dual-band film systems often exhibit strong passband ripples and residual reflection peaks in the transition zone, making it difficult to stably reduce the reflectivity at 1064nm to below 0.1%. Furthermore, reducing the absorption pressure of the 532nm high-reflectivity film stack to below 10ppm requires eliminating metastable absorption defects in the film and suppressing nonlinear absorption effects, which is difficult to achieve stably with existing technologies.

[0004] In summary, there is an urgent need to develop a harmonic separation mirror suitable for high-power green laser systems, which has comprehensive performance characteristics such as reflectivity >99.9% at 532nm, reflectivity <0.1% at 1064nm, absorption <10ppm at 532nm, and temperature rise <35℃ at high power, in order to overcome the current technical bottlenecks. Summary of the Invention

[0005] To address the aforementioned problems, this invention provides a harmonic separation mirror suitable for high-power lasers.

[0006] The present invention provides a harmonic separation mirror suitable for high-power lasers, which adopts the following technical solution: A harmonic separation mirror suitable for high-power lasers includes a substrate and a film system, wherein the film system is located on one side of the substrate, characterized in that the film system structure of the harmonic separation mirror suitable for high-power lasers is Air|(LH). 15 |Sub;wherein, Sub represents the substrate, Air represents air, (LH) 15 The system is defined as follows: H represents an HfO2 film layer, and L represents a SiO2 film layer. The film system comprises 30 alternating layers of high-refractive-index and low-refractive-index films stacked from the substrate outwards. The geometric thicknesses of layers 1-30 are as follows: layer 1: 49.68 nm, layer 2: 92.66 nm, layer 3: 76.73 nm, layer 4: 95.33 nm, layer 5: 55.14 nm, layer 6: 91.02 nm, layer 7: 73.59 nm, layer 8: 93.63 nm, layer 9: 59.84 nm, layer 10: 91.14 nm, layer 11: 70.41 nm, layer 12: 91.37 nm, layer 3: 91.37 ...1.37 nm, layer 5: 91.37 nm, layer 6: 91.37 nm, layer 7: 91.37 nm, layer 8: 91.37 nm, layer 9: 91.37 nm, layer 9: 91.37 nm, layer 10: 91.14 nm, layer 11: 70.41 nm, layer 12: 91.37 nm, layer 3: 91.37 nm, layer 13: 91.37 nm, layer Layer 13: 63.58nm; Layer 14: 93.21nm; Layer 15: 67.21nm; Layer 16: 88.33nm; Layer 17: 66.97nm; Layer 18: 96.42nm; Layer 19: 64.19nm; Layer 20: 84.22nm; Layer 21: 70nm; Layer 22: 100.57nm; Layer 23: 62nm; Layer 24: 78.77nm; Layer 25: 72.54nm; Layer 26: 105.11nm; Layer 27: 61.14nm; Layer 28: 71.99nm; Layer 29: 74.63nm; Layer 30: 192.81nm.

[0007] Furthermore, the substrate is Hellish S300 high-purity synthetic fused silica.

[0008] Furthermore, the film system is deposited on the substrate using ion beam assisted deposition and / or magnetron sputtering deposition processes.

[0009] Furthermore, in the ion beam assisted deposition process for depositing the HfO2 film, the ion beam voltage of the auxiliary ion source is 300-500V, the ion beam current is 100-200mA, and the working partial pressure of high-purity oxygen is controlled at 1.5×10⁻⁶. -2 Pa-3.0×10 -2 Pa.

[0010] Furthermore, in the magnetron sputtering deposition process for depositing SiO2 film, the sputtering target used is a silicon target with a purity of 99.99%, and the working gas is a mixture of argon and high-purity oxygen.

[0011] Furthermore, the flow rate-to-volume ratio of argon to high-purity oxygen is 1:2-1:5, and the sputtering working pressure is 0.1Pa-0.5Pa.

[0012] Furthermore, the deposition rate of the SiO2 film is 0.2 nm / s-1.0 nm / s.

[0013] Furthermore, the harmonic separator suitable for high-power lasers has an average reflectivity greater than 99.9% at a wavelength of 532nm, an average reflectivity less than 0.1% at a wavelength of 1064nm, and an absorption loss of less than 10ppm at a wavelength of 532nm.

[0014] In summary, the present invention has the following beneficial effects: 1. This invention, by optimizing the film structure, overcomes the limitations of traditional periodic film stacks and eliminates the strong passband interference ripples caused by interface phase mismatch. While ensuring that the reflectivity of 532nm frequency-doubled light is greater than 99.9%, the surface residual reflectivity of 1064nm fundamental frequency light is stably suppressed to below 0.1%, which greatly improves the separation efficiency of the frequency-doubled link of the laser system. 2. This invention, through controlling the hybrid vapor deposition process of the film system, ensures that the product's minimal absorption loss in the 532nm wavelength band is consistently below 10ppm; when subjected to 5000W high-power continuous laser irradiation, the device's operating temperature rise is controlled below 35℃, solving the problems of thermal lensing effect and wavefront distortion easily caused by traditional devices; at the same time, it ensures a high film density, resulting in a LIDT as high as 22.5J / cm². 2 This ensures the long-term stable operation of the high-energy solid-state laser system. Attached Figure Description

[0015] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0016] Figure 1 This is a schematic diagram of the structure of the harmonic separation mirror of Embodiment 1 of the present invention, applicable to high-power lasers; Figure 2 This is a transmittance-wavelength curve of the harmonic separation mirror for high-power lasers in Embodiment 1 of the present invention, where the horizontal axis is wavelength and the vertical axis is transmittance. Figure 3 This is a scan test diagram of the small absorption loss of the harmonic separator mirror suitable for high-power lasers in Embodiment 1 of the present invention at a wavelength of 532nm. Detailed Implementation

[0017] The present invention will be described in detail below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.

[0018] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials and reagents used in the following examples are all available through conventional commercial channels.

[0019] The high-purity synthetic fused silica substrate was selected from Herlix S300. Example 1

[0020] Combination Figure 1 A harmonic separation mirror suitable for high-power lasers includes a substrate and a membrane system, wherein the membrane system is located on one side of the substrate; The film system comprises 30 alternating layers of high-refractive-index and low-refractive-index films, arranged from the substrate outwards according to the film system structure. The film system structure is as follows: substrate / 49.68nmH, 92.66nmH, 76.73nmH, 95.33nmH, 55.14nmH, 91.02nmH, 73.59nmH, 93.63nmH, 59.84nmH, 91.14nmH, 70.41nmH, 91.37nmH, 63 0.58nmH, 93.21nmH, 67.21nmH, 88.33nmH, 66.97nmH, 96.42nmH, 64.19nmH, 84.22nmH, 70nmH, 100.57nmH, 62nmH, 78.77nmH, 72.54nmH, 105.11nmH, 61.14nmH, 71.99nmH, 74.63nmH, 192.81nmH / air; Wherein, H is a high refractive index film layer, and L is a low refractive index film layer. In this embodiment, H is an HfO2 film layer, and L is a SiO2 film layer. The substrate is selected as Herlich S300 high-purity synthetic fused silica. Before coating, the substrate needs to be ultrasonically cleaned for 15 minutes each in anhydrous ethanol, deionized water (resistivity ≥18.2MΩ·cm), and deionized water containing alkaline optical detergent, with an ultrasonic frequency of 40kHz. After cleaning, it is slowly lifted to dehydrate and placed in a dust-free oven at 120℃ to dry for 2 hours. Then it is quickly transferred to the vacuum chamber of the vacuum coating machine for later use.

[0021] The film system was deposited on the substrate using a vacuum deposition method. The HfO2 film was deposited via ion beam-assisted vapor deposition. During evaporation, pure metallic Hf was used as the evaporation raw material, and high-purity oxygen (99.999% purity) was introduced as the reaction gas. Simultaneously, an ion beam bombarded the film surface, increasing atomic mobility and promoting densification, allowing the evaporated Hf atoms to fully react with O2 to form HfO2. Specific process parameters were controlled as follows: the ion beam voltage of the auxiliary ion source was controlled at 400V, the ion beam current at 150mA, and the working partial voltage of the high-purity oxygen was controlled at 2.0 × 10⁻⁶. -2 Pa, which enables it to form a high-density, high-refractive-index film, effectively replenishing the oxygen deficiency during the film formation process and reducing metastable absorption defects; The SiO2 film was deposited using magnetron sputtering deposition, with a 99.99% pure silicon (Si) target as the sputtering target material. The working gas was a mixture of argon and high-purity oxygen. During the sputtering process, the sputtered Si atoms fully combined with the reactive gas O2 to generate SiO2. The specific process parameters were controlled as follows: the flow-volume ratio of argon to high-purity oxygen was controlled at 1:3, the sputtering working pressure was controlled at 0.3 Pa, and the deposition rate was controlled at 0.5 nm / s, resulting in a dense low-refractive-index film that effectively alleviated the thermal mismatch of film stacking. After the film deposition is completed, the harmonic separation mirror is subjected to high-temperature annealing in a muffle furnace. The specific process parameters are controlled as follows: under atmospheric conditions, the mirror is heated to 300°C at a heating rate of 2°C / min, held for 8 hours, and then cooled to room temperature at a rate of 1°C / min to obtain the separation mirror sample.

[0022] The transmittance of the sample prepared in Example 1 was measured using a high-performance spectrophotometer (PerkinElmer Lambda 950). Figure 2 As shown in the transmittance-wavelength curve, the sample of Example 1 exhibits an extremely deep "U-shaped" transmission valley in the 532nm band, and the measured transmittance at 532nm approaches 0. Its actual reflectance R > 99.94%, which fully meets the high reflectance requirement of frequency doubling light refraction. At the same time, in the 1000nm-1100nm band, the transmission curve is extremely smooth with no obvious passband ripples. The transmittance measured at 1064nm is as high as 99.92%, and the corresponding residual surface reflectance is only 0.08%.

[0023] A weak absorber based on the co-thermal deflection interference principle was used, with a 532nm continuous laser as the pump source, to perform two-dimensional grid scanning on the sample surface of Example 1 (scanning distance 0-2.8mm). Combination Figure 3As can be seen from the scanned absorption spectrum at a wavelength of 532 nm, the scanned absorption spectrum of Example 1 exhibits extremely excellent low absorption characteristics. Its basic absorption background value is maintained at around 1.2 ppm, and the extreme absorption peak in the scanned region is only 6.5-6.8 ppm. The overall absorption loss is stable at <10 ppm.

[0024] A continuous 532nm green laser with an output power of 5000W was used to continuously irradiate the center of the sample in Example 1 for 2 hours with a spot diameter of 2.0mm. The temperature rise and reflected wavefront distortion (PV value) were monitored in situ using an infrared thermal imager and a laser interferometer. After continuous irradiation reaches thermal equilibrium, the highest temperature rise in Example 1 is only +28.2℃, which is effectively controlled within +35℃ of the substrate surface temperature rise. Furthermore, the reflected wavefront distortion is minimal (PV < λ / 10), and no thermal lensing effect occurs.

[0025] According to the ISO 21254 international standard, a Q-switched pulsed laser with a wavelength of 532nm and a pulse width of 10ns was used to conduct a 10000-on-1 damage threshold test. The LIDT threshold measured in Example 1 was 22.5 J / cm², and it exhibited extremely high structural stability under high-energy green light cyclic irradiation, with a dense film layer and no peeling. Example 2

[0026] A harmonic separation mirror, whose overall layer structure and magnetron sputtering process for the SiO2 film are basically the same as in Example 1, differs only in the control of the process parameters for the HfO2 film: the HfO2 film is also deposited using pure metallic Hf as raw material via ion beam assisted deposition, but the working partial pressure of high-purity oxygen is set to 0.5 × 10⁻⁶. -2 Pa.

[0027] A weak absorber based on the co-thermal deflection interference principle was used, with a 532nm continuous laser as the pump source, to perform two-dimensional grid scanning on the sample surface of Example 2 (scanning distance 0-2.8mm); The measured average absorbance of the sample in Example 2 soared to 65.4 ppm. This may be because the Hf feedstock could not be fully oxidized during ion-assisted evaporation, resulting in a large amount of HfO in the film. 2-x Metastable absorption defects lead to a sharp increase in absorption loss at 532nm.

[0028] A continuous 532nm green laser with an output power of 5000W was used to continuously irradiate the center of the sample in Example 2 with a spot diameter of 2.0mm, and the temperature rise and reflected wavefront distortion (PV value) were monitored in situ by an infrared thermal imager and a laser interferometer. The sample in Example 2, with its high absorption characteristics, experienced a maximum temperature rise exceeding +187°C after only 15 minutes of irradiation. This resulted in significant thermal stress within the film layer, causing a severe thermal lensing effect and leading to severe distortion of the reflected beam (PV > λ / 2), which failed to meet the damage resistance requirements of high-power lasers. Example 3

[0029] A harmonic separation mirror, whose overall layer structure and auxiliary deposition process of HfO2 film are basically the same as in Example 1, the only difference is that the process parameters of SiO2 film are controlled differently: the SiO2 film is also deposited by magnetron sputtering using a silicon target, but the flow-volume ratio of argon to high-purity oxygen is controlled at 1:1 and the sputtering working pressure is controlled at 0.8 Pa.

[0030] According to the ISO 21254 international standard, a Q-switched pulsed laser with a wavelength of 532 nm and a pulse width of 10 ns was used to perform a 10000-on-1 damage threshold test on the sample of Example 3. The LIDT threshold measured in Example 3 dropped sharply to 6.5 J / cm. 2 During the laser shock test, large-area film peeling failure occurred, exhibiting low structural stability.

[0031] This may be because, under these conditions, the excessively high working pressure causes the sputtered Si atoms to collide violently before reaching the substrate, resulting in a significant decrease in kinetic energy. This leads to a loose structure and reduced aggregation density of the generated SiO2 film, which severely reduces the physical strength and environmental stability of the film under high-power laser shock.

[0032] Comparative Example 1 A harmonic separation mirror, whose HfO2 and SiO2 coating process parameters and deposition method are basically the same as those in Example 1, the only difference being that the geometric thickness of the 30th layer of the film system is controlled to be 92.00 nm.

[0033] The transmittance of the sample prepared in Comparative Example 1 was measured using a high-performance spectrophotometer (PerkinElmer Lambda 950). The sample in Comparative Example 1 exhibited strong passband ripples near the 1064nm transition band, and the surface residual reflectance measured at 1064nm was 2.85%, failing to achieve the high transmittance index of extremely low reflectance.

[0034] The above are all modifications that can be made to this embodiment without contributing any inventive step, or solutions that clearly constitute technical teaching, after reading this specification. However, as long as they are within the scope of the claims of this invention, they should be protected by patent law.

Claims

1. A harmonic separation mirror suitable for high-power lasers, comprising a substrate and a film system, wherein the film system is located on one side of the substrate, characterized in that, The membrane structure of the harmonic separation mirror suitable for high-power lasers is Air|(LH). 15 |Sub;wherein, Sub represents the substrate, Air represents air, (LH) 15 The system is defined as follows: H represents an HfO2 film layer, and L represents a SiO2 film layer. The film system comprises 30 alternating layers of high-refractive-index and low-refractive-index films stacked from the substrate outwards. The geometric thicknesses of layers 1-30 are as follows: layer 1: 49.68 nm, layer 2: 92.66 nm, layer 3: 76.73 nm, layer 4: 95.33 nm, layer 5: 55.14 nm, layer 6: 91.02 nm, layer 7: 73.59 nm, layer 8: 93.63 nm, layer 9: 59.84 nm, layer 10: 91.14 nm, layer 11: 70.41 nm, layer 12: 91.37 nm, layer 3: 91.37 ...1.37 nm, layer 5: 91.37 nm, layer 6: 91.37 nm, layer 7: 91.37 nm, layer 8: 91.37 nm, layer 9: 91.37 nm, layer 9: 91.37 nm, layer 10: 91.14 nm, layer 11: 70.41 nm, layer 12: 91.37 nm, layer 3: 91.37 nm, layer 13: 91.37 nm, layer Layer 13: 63.58nm; Layer 14: 93.21nm; Layer 15: 67.21nm; Layer 16: 88.33nm; Layer 17: 66.97nm; Layer 18: 96.42nm; Layer 19: 64.19nm; Layer 20: 84.22nm; Layer 21: 70nm; Layer 22: 100.57nm; Layer 23: 62nm; Layer 24: 78.77nm; Layer 25: 72.54nm; Layer 26: 105.11nm; Layer 27: 61.14nm; Layer 28: 71.99nm; Layer 29: 74.63nm; Layer 30: 192.81nm.

2. The harmonic separation mirror suitable for high-power lasers according to claim 1, characterized in that, The substrate is a high-purity synthetic fused silica substrate.

3. The harmonic separation mirror suitable for high-power lasers according to claim 1, characterized in that, The film system is deposited on the substrate using ion beam assisted deposition and / or magnetron sputtering deposition processes.

4. The harmonic separation mirror suitable for high-power lasers according to claim 3, characterized in that, In the ion beam assisted deposition process for depositing HfO2 films, the ion beam voltage of the auxiliary ion source is 300-500V, the ion beam current is 100-200mA, and the working partial pressure of high-purity oxygen is controlled at 1.5×10⁻⁶. -2 Pa-3.0×10 -2 Pa.

5. The harmonic separation mirror suitable for high-power lasers according to claim 3, characterized in that, In the magnetron sputtering deposition process, when depositing the SiO2 film, the sputtering target used is a silicon target with a purity of 99.99%, and the working gas is a mixture of argon and high-purity oxygen.

6. The harmonic separation mirror suitable for high-power lasers according to claim 5, characterized in that, The flow rate-to-volume ratio of argon to high-purity oxygen is 1:2-1:5, and the sputtering working pressure is 0.1Pa-0.5Pa.

7. The harmonic separation mirror suitable for high-power lasers according to claim 5, characterized in that, The deposition rate of the SiO2 film is 0.2 nm / s-1.0 nm / s.

8. The harmonic separation mirror suitable for high-power lasers according to claim 1, characterized in that, The harmonic separator suitable for high-power lasers has an average reflectivity greater than 99.9% at a wavelength of 532nm, an average reflectivity less than 0.1% at a wavelength of 1064nm, and an absorption loss of less than 10ppm at a wavelength of 532nm.

Citation Information

Patent Citations

  • Light emitting diode chip and manufacturing method thereof

    CN112840467A

  • Chirp reflector and preparation method

    CN121028266A